(untitled) (Communications in Computational Physics, 2009)
The effect of the equilibrium pair separation on the evolution of cluster structures is investigated based on a new proposed pair potential. The computational results demonstrate that the potential with large equilibrium pair separation stabilizes decahedra and close-packed structures, while disordered structures appear for the potential with small equilibrium pair separation. The icosahedral clusters are dominated in the middle range of equilibrium pair separation. For the small size clusters (N≤24) the dominated structural motif is the polytetrahedra, which is almost independent of the details of the potential.